2012
DOI: 10.1007/s13410-012-0086-y
|View full text |Cite
|
Sign up to set email alerts
|

Anti-diabetic activity of oryzanol and its relationship with the anti-oxidant property

Abstract: Experimental evidence suggests that oxidative stress induced by streptozotocin (STZ) damage the pancreatic beta cells and produce hyperglycemia in rats. The current study was initiated to investigate the effects of oryzanol (OZ), a commercially-important bioactive phytochemical isolated from crude rice bran oil (cRBO) against experimental diabetes as well as the antioxidant potential of the drug. OZ was isolated by a two-step solvent crystallization process from cRBO, which was extracted from fresh rice bran b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 30 publications
1
27
0
Order By: Relevance
“…Different studies suggested that ORY could exert its antioxidant effects by modulating the endogenous antioxidant enzyme activities. In particular, SOD has been found to be positively regulated by ORY [ 26 , 33 , 34 ]. Here, we evaluated the protein expression and activity of SOD enzymes in the presence of ORY 24h alone or followed by oxidative insult.…”
Section: Resultsmentioning
confidence: 99%
“…Different studies suggested that ORY could exert its antioxidant effects by modulating the endogenous antioxidant enzyme activities. In particular, SOD has been found to be positively regulated by ORY [ 26 , 33 , 34 ]. Here, we evaluated the protein expression and activity of SOD enzymes in the presence of ORY 24h alone or followed by oxidative insult.…”
Section: Resultsmentioning
confidence: 99%
“…In Drosophila melanogaster model, γ-oryzanol enhanced antioxidant defense by significantly improving the antioxidant enzymes such as SOD, CAT, and GST, and decreasing the malondialdehyde (MDA) and ROS production [ 205 ]. In streptozotocin-induced oxidative stress, γ-oryzanol also effectively increased the levels of SOD and reduced glutathione in rats [ 206 ]. In mice model of ethanol-induced liver injury, γ-oryzanol was able to prevent increased hepatic lipid hydroperoxide, TBARS levels as well as plasma aspartate and alanine aminotransferase activities.…”
Section: γ-Oryzanol: Structure-antioxidant Activity Relationshipmentioning
confidence: 99%
“…Furthermore, GO‐treated mice better recovered from an ethanol‐induced decrease in the hepatic glutathione level together with enhancing superoxide dismutase activity. GO effectiveness in ameliorating streptozotocin‐induced oxidative stress in rats (Ghatak and Panchal, ) is detailed in the chapter concerning diabetes management.…”
Section: Gamma‐oryzanol – a Powerful Antioxidantmentioning
confidence: 99%